The Revocation of Corruptors’ Political Rights in Indonesian Legal System - Sugiharto, Imawan; Asmarudin, Imam (International Journal of Engineering and Technology, 2018)
The Indonesian government experiences constant shocks as some state actors at central and regional levels, either of executive, legislative or judicative bodies, are adjudicated for corruption cases. As it is considered as an extraordinary crime, the Corruption Eradication Commission (Komisi Pemberantasan Korupsi or KPK) made a legal breakthrough by imposing punishment in addition to principal punishment for a deterrent effect. The said additional punishment is in the form of revocation of corruptors political rights as conducted by Criminal Corruption Judge and confirmed by Decision of the Supreme Court of the Republic of Indonesia. However, this decision creates a polemic because of the existence of Decision of Constitutional Court of the Republic of Indonesia which cannot annul punishment in the form of revocation of citizens political rights, for it is considered contradictory to the 1945 Constitution of the Republic of Indonesia. There is an overlapping between the Decision of the Supreme Court of the Republic of Indonesia with the Decision of the Constitutional Court of the Republic of Indonesia stating that such revocation of political rights violates the human rights. Our contention is that overlapping authorities and impacts of revocation of political rights require an additional legal instrument. This is important to ensure the mechanism of the revocation aligns with the human rights and exhibits a progressive legal movement in eradicating corruption.Â